Réponses

2012-10-16T22:45:52+02:00

Hello,

 

Si on prend 4 et -7.

 

La somme des deux :

 

4 + (-7) = 4 - 7 = -3

 

Le produit des deux :

 

4 * (-7) = -28

 

Bingo =)

 

Au plaisir.

2012-10-16T23:19:23+02:00

x+y=-3 et xy=-28

y=-3-x et x(-3-x)=-28 => -3x-x²=-28 => x²+3x-28=0

x²+3x-28=0 est de la forme ax²+bx+c=0

∆=b²-4ac=(3)²-4(1)(-28)=9+112=121=11² donc ∆>0 => 2 solutions x₁ et x₂

x₁=(-b-√∆)2a=(-3-11)/(2(1))=-14/2=-7

x₂=(-b+√∆)2a=(-3+11)/(2(1))=8/2=4

si x=-7 alors y=-3-(-7)=-3+7=4

si x=4 alors y=-3-4=-7

les solutions sont 4 et -7